Quality of Life of Non-Cash Food Assistance Beneficiary Families in Gedangsewu Village, Boyolangu Subdistrict, Tulungagung Regency - Herviansyah, Maulana; Yuliani, Dwi; Haryani, Ayii (Pekerjaan Sosial, 2024)
Quality of life refers to an individual's perception of their position in life within the context of the culture and value systems in which they live, and their relationship to their goals, expectations, standards, and concerns. This study aims to empirically capture: 1) respondent characteristics, 2) physical health, 3) psychological conditions, 4) social relationships, and 5) the environment of Non-Cash Food Aid (BPNT) recipient families. The method used is a survey method with a descriptive approach. The sampling technique employed is Simple Random Sampling. Data collection techniques used are: 1) questionnaires and 2) documentation studies. The validity and reliability tests of the measuring instruments in this study used readability tests, face validity, and SPSS analyzed with descriptive statistics. The study results on 56 BPNT recipient families showed that the quality of life of the recipients falls into the medium category, with a total score ranging from 50 to 75. Based on the study results, the recipients are aware of the importance of maintaining physical health, have very close social relationships, good social support, and a comfortable environment. However, problems were identified in psychological conditions, marked by frequent negative feelings, rarely feeling happy, dissatisfaction with enjoying life, and infrequent opportunities for fun or recreation. Financial uncertainty, lack of income, and debt burdens can cause psychological stress for the recipients. The researchers propose a Quality of Life Improvement Program for recipient families through the Joint Business Group (KUBE) Catfish Farming with the Biofloc System. This program uses the group work method with a recreation skill group type. The strategy employed is collaboration, and the technique used is capacity building.